2022
DOI: 10.1021/jacs.2c05044
|View full text |Cite
|
Sign up to set email alerts
|

A Base-Promoted Reductive Coupling Platform for the Divergent Defluorofunctionalization of Trifluoromethylarenes

Abstract: We report a trifluoromethylarene reductive coupling method that dramatically expands the scope of difluorobenzylic substructures accessible via C−F bond functionalization. Catalytic quantities of a Lewis base, combined with a disilane reagent in formamide solvent, promotes the replacement of a single trifluoromethyl fluorine atom with a silylated hemiaminal functional group. The reaction proceeds through a difluorobenzyl silane intermediate that can also be isolated. Together, these defluorinated products are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…2 Among the organofluorine motifs, -CF 3 groups are the most common, which likely stems from available synthetic methods and the wide abundance of trifluoromethylating sources such as Me 3 Si-CF 3 , 4,5 and related radical 6 and electrophilic reagents. 7 In contrast, there are significantly fewer routes to install internal C-F bonds, [8][9][10][11][12][13][14][15][16][17] some of which require potentially explosive reagents (deoxyfluorination). 18 A consequence of limited general synthetic strategies to access ArCF 2 -R motifs is that although several promising bioactive compounds contain ArCF 2 -R groups (Fig.…”
mentioning
confidence: 99%
“…2 Among the organofluorine motifs, -CF 3 groups are the most common, which likely stems from available synthetic methods and the wide abundance of trifluoromethylating sources such as Me 3 Si-CF 3 , 4,5 and related radical 6 and electrophilic reagents. 7 In contrast, there are significantly fewer routes to install internal C-F bonds, [8][9][10][11][12][13][14][15][16][17] some of which require potentially explosive reagents (deoxyfluorination). 18 A consequence of limited general synthetic strategies to access ArCF 2 -R motifs is that although several promising bioactive compounds contain ArCF 2 -R groups (Fig.…”
mentioning
confidence: 99%
“…Deconstruction of already prepared C−F bonds is an alternative strategy that has gained prominence as an attractive tool to form fluorinated motifs [28–37] . Most sp 3 C−F bonds have strong bonds (BDEs ranging from 97 to 131 kcal/mol), [8,38] rendering them resistant to unassisted C−F cleavage/addition reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[22,25] Deconstruction of already prepared CÀ F bonds is an alternative strategy that has gained prominence as an attractive tool to form fluorinated motifs. [28][29][30][31][32][33][34][35][36][37] Most sp 3 CÀ F bonds have strong bonds (BDEs ranging from 97 to 131 kcal/mol), [8,38] rendering them resistant to unassisted CÀ F cleavage/addition reactions. Thus, compared to CÀ Br and CÀ I bonds, the participation of CÀ F bonds in S N 2 pathways is far less common.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this strategy is not without its own disadvantages, including the use of fluoride reagents and expensive crown ethers. Moreover, the authors have reported only two products, with low selectivity and yields (less than 50%).Sustainable and eco-friendly synthetic approaches proceeded by the main-group species have gained recent significant attention [35][36][37][38][39][40][41][42][43][44] . Thus, we sought the method leading to versatile germanium compounds that blends the high selectivity of TM-mediated approaches with the practicality of a base-promoted protocol.…”
mentioning
confidence: 99%
“…Sustainable and eco-friendly synthetic approaches proceeded by the main-group species have gained recent significant attention [35][36][37][38][39][40][41][42][43][44] . Thus, we sought the method leading to versatile germanium compounds that blends the high selectivity of TM-mediated approaches with the practicality of a base-promoted protocol.…”
mentioning
confidence: 99%